P02 Outcome of mild traumatic brain injury (tbi) in children- results from a prospective uk cohort study. (27th April 2015) - Sharples, P; Hollen, L; Emond, A
Abstract : Aim: To use prospectively collected data to investigate the outcomes up to 16 years of TBI in childhood. Methods: Data from the Avon Longitudinal Study of Parents and Children (ALSPAC) were analysed. Background demographics and developmental and behavioural profile of the children were derived from questionnaires completed by the mother in pregnancy, at 6 weeks and at 18 and 42 months. Injury data were derived from questionnaires completed by the child's carer at 4½ 5½ 6½ 8 ½ and 11½ years of age. Outcomes were collected when the child was 11–16 years old, from ALSPAC questionnaires and research clinics, and from linked educational data. TBI cases (n = 410), defined as any head injury resulting in loss of consciousness and/or a skull fracture before the age of 11, were compared with children of the same age (n = 1819) who suffered traumatic orthopaedic injuries (fractures- excluding skull fractures). Controls (n = 8770) were all children with available injury data who did not have a TBI or orthopaedic injury. Results: 410 ALSPAC participants (59% male) had a TBI before 11; 154 (38%) had a fractured skull, and 36 (9%) had multiple TBIs. Orthopaedic injuries were reported for 1819 participants (52% male) before 11. Compared to controls, children who had a TBI came from families living in adversity, with mothers with lower educational qualifications and a history of depression. The children who suffered a TBI had higher hyperactivity and conduct scores age 42 months, but no differences were apparent for those who later suffered orthopaedic injuries. Outcomes at 13–16 which remained associated with TBI after adjustment were the total behavioural problems score, the hyperactivity score and the conduct problems score of the SDQ, and high levels of anxiety and depression. Adjustment for pre-injury SDQ scores attenuated the associations with the SDQ scores but these remained significantly different from controls. Weak associations were also observed between orthopaedic injuries and later conduct problems. Conclusions: TBI in childhood was associated with increased behavioural problems up to 16 years, and increased hyperactivity and conduct problems which were not explained by pre-injury characteristics. Depression and anxiety were also more common in TBI survivors.